2017
DOI: 10.1016/j.watres.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Removal of bromide from surface waters using silver impregnated activated carbon

Abstract: The main objectives of this study were to develop an understanding of silver impregnated activated carbon (SIAC) preparation for enhanced bromide (Br) removal from water, and to investigate the impact of aqueous background composition on the Br removal. Several SIACs were produced using various combinations of oxidation and silver impregnation procedures and powdered activated carbons (ACs). Regardless of the preparation procedure, SIACs showed significantly Br uptakes than the virgin ACs. The Br removal effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(9 citation statements)
references
References 21 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…(NT) samples. Although some recent studies have reported excellent bromide removal for SIAC, it is still unclear if the removal capacity is dependent on NOM properties (Chen et al 2017, Watson et al 2016. The main objective of this study, was to compare SIAC to more conventional treatments, and to determine, in general, how different water treatment protocols responded to different NOM sources, with all other water quality parameters being kept constant, in terms of NOM and bromide removal, and DBP formation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…(NT) samples. Although some recent studies have reported excellent bromide removal for SIAC, it is still unclear if the removal capacity is dependent on NOM properties (Chen et al 2017, Watson et al 2016. The main objective of this study, was to compare SIAC to more conventional treatments, and to determine, in general, how different water treatment protocols responded to different NOM sources, with all other water quality parameters being kept constant, in terms of NOM and bromide removal, and DBP formation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…EC/SIAC remained highly efficient for bromide adsorption regardless of NOM source or concentration. A recent study of bromide adsorption onto silver-impregnated PAC found that bromide removal efficiency was affected by water composition (NOM and chloride concentration) as well as silver content and surface area of the SIAC (Chen et al 2017).…”
Section: Doc and Bromide Removalmentioning
confidence: 99%
“…Activated carbon adsorption is characterized by a low level of Brremoval efficiencies (22-30%) (Watson et al, 2016). Therefore, various concepts have been developed to improve their removal efficiencies, most notably the development and use of silver impregnated activated carbons (Ateia et al, 2019;Chen et al, 2017;Rajaeian et al, 2018). Although results in the range of 40-90% were reported in the presence of background anions, specifically chloride and natural organic matter (NOM) negatively affected Brremoval rates (Ateia et al, 2019;Chen et al, 2017;Krasner et al, 2016;Watson, K., Farré M.J., Knight, 2012;Watson et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various concepts have been developed to improve their removal efficiencies, most notably the development and use of silver impregnated activated carbons (Ateia et al, 2019;Chen et al, 2017;Rajaeian et al, 2018). Although results in the range of 40-90% were reported in the presence of background anions, specifically chloride and natural organic matter (NOM) negatively affected Brremoval rates (Ateia et al, 2019;Chen et al, 2017;Krasner et al, 2016;Watson, K., Farré M.J., Knight, 2012;Watson et al, 2016). It is also noteworthy that although conventional treatment and activated carbon adsorption processes remove NOM while failing to remove Brfrom water, the result was an elevated Br -:DOC ratio and an increased formation of brominated-DBPs in the treated water (e.g., Metcalfe et al, 2015;Phetrak et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…during coagulation, termed silver-amended coagulation. Previous studies revealed that silver impregnated adsorbents (e.g., Ag-doped carbon aerogels, activated carbon and polymeric cloth) could effectively remove Brfrom waters (Sánchez- Polo et al 2006, Gong et al 2013, Chen et al 2017, Polo et al 2016. However, silver impregnation on pre-oxidized carbon surfaces requires multiple synthesis steps, and Brremoval depends on the dispersion and the availability of silver solids on the adsorbent surface.…”
Section: Introductionmentioning
confidence: 99%